Reducing stigmatization among persons with mental illness: challenges for the psychiatric social workers (2015)
The stigmatization of persons with mental illness has been found to have a negative impact on people with serious psychological problems. The literature reviewed suggested that the way in which the general public perceives people with mental health problems depends on their diagnosis. Those with schizophrenia are seen as dangerous and unpredictable. The negative consequences of this stigmatization require psychiatric social workers to embark on strategies towards reducing the stigma associated with persons having mental illness. A review of some relevant literature also revealed that mental health stigma has been found to have negative impact on an individual’s opportunities for jobs and lodging, self esteem, environmental mastery, autonomy, self-growth, unwillingness to seek professional and psychological help. Therefore, the paper examined the nature, types and treatment of mental illness. It also discussed the effects of stigma on persons having mental illness and the various ways by which it can be reduced. Such ways include: protestation, contact and education. The paper recommends that Government at all levels should plan and execute health education programmes. It is also recommended that community mental homes should be sited in all communities with a view to saving anybody with symptoms of mental illness prompt and adequate medical treatment